Focus on writing : - Kirszner, Laurie G. (Bedford/St. Martins, 2008)
Focus on Writing: Paragraphs and Essays, new from best-selling authors Laurie Kirszner and Stephen Mandell, is their most accessible writing text yet. Focus on Writing engages students visually, demonstrates concepts with color and highlighting, and offers students more grammar support than any comparable text on the market.